Physical chemistry. - Singh, N. B. (New Age International, 2009)
About the Book: This is a comprehensive book of Physical Chemistry especially written for B. Sc. II year and B. Sc. III year students of Indian universities based on the model syllabus prepared by UGC, New Delhi. The book is written in a simple language and gives a comprehensive detail of the subject with latest developments. There are 11 Chapters in the book. The book is equally useful to students and teachers. Some special Chapters like Surface Chemistry-Adsorption and Surface Topography, Molecular Spectroscopy and Diffraction Techniques have also been included in this book. Contents: Thermodynamics-I Thermodynamics-II Solutions Phase Equilibria, Phase Diagrams and Distribution Law Chemical Equilibrium Photochemistry Electrochemistry-I Electrochemistry-II Molecular Spectroscopy Surface Chemistry-Adsorption and Surface Topography Diffraction Techniques.